Charakterystyka postu w euchologii okresu przygotowania paschalnego w "Mszale hiszpańsko-mozarabskim" z 1991 roku - Porosło, Krzysztof (Verbum Vitae, 2025)
The author of this article aims to show the characteristics of the Paschal preparation period of the Hispanic-Mozarabic rite, especially with regard to the practice of abstinence from meat and fasting. To this end, the history of the formation of this liturgical period in the first millennium is presented and the characteristic features of Lent in the Spanish tradition which are partially shared with other liturgical traditions of both the West and the East. The unique theology of the Lenten period of preparation for Pascha in the Visigothic tradition was also influenced by the theology of St. Isidore of Seville, which left its mark on Spanish Mass euchology. At the heart of the article, then, is the presentation of the theology of fasting that stems from an analysis of the Lenten orations of the Missale Hispano-Mozarabicum. The 40-day fast, following the example of the fasts of Moses, Elijah and Jesus himself, is understood in the Spanish rite as a sacrifice offered to God and intercession for the living and the dead, as a remedy for sins and an effective means of spiritual warfare against the Devil, as an instrument of our sanctification and preparation for Pascha, or, finally, as the opposite of Adam’s and Eve’s Edenic sin of gluttony and failure to fast. The period of quadragesimae and abstinence during this time is a tithe of the entire year that every Christian should offer to God.